ESSENTIAL FEATURES OF PHRASEOLOGICAL UNITS: SEMANTIC AND STRUCTURAL FEATURES - Seytimbetova Aykumar Pulatbaevna (Western European Studies, 2023)
This article tries more or less fully, to cover the issues of researching the semantics, structure and functions of phraseological units. The linguistic structure of the work, one of the elements of which is the phraseological composition of the vocabulary, is a multifunctional author's fragments of which are verbalized in a phraseological sign and reflect the mental operations of the author who creates the artistic word
Keywords: Semantic and structural features; a certain phenomenon of reality